2004
DOI: 10.1017/s0021859604003946
|View full text |Cite
|
Sign up to set email alerts
|

Herbage production and animal performance on perennial ryegrass/white clover dairy pastures under alternative spring grazing managements

Abstract: Spring grazing managements which allowed some early inflorescence development, followed by hard grazing in order to remove the reproductive stems (designated ‘late control’), were compared with a conventional close grazing strategy (‘early control’) in three paddock-scale complete randomized block studies with dairy cows grazing perennial ryegrass/white clover pastures during consecutive years (1990–1993) in Palmerston North, New Zealand. Experiment 1 was designed to evaluate the timing of late control, Expt 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Unfortunately, few studies have reported tiller survival and production in temperate grasses – almost none in subtropical environments – which restricts the possibilities for comparisons. In temperate NZ, perennial ryegrass swards showed a high proportion of reproductive tillers (from 25% to 70%), a marked tiller population turnover at flowering, and an overall increase in total tiller density (Matthew et al ., ; Hernández‐Garay et al ., ; Bahmani et al ., ; Da Silva et al ., ), which is consistent with the reproductive perennation pathway being dominant. Although there is evidence that this may differ among cultivars (Bahmani et al ., ) and that tiller density can be manipulated through grazing (Thom, ; Hernández‐Garay et al ., ; Da Silva et al ., ), management appears to have little influence on the persistence strategy of perennial ryegrass (Korte, ; Matthew et al ., ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Unfortunately, few studies have reported tiller survival and production in temperate grasses – almost none in subtropical environments – which restricts the possibilities for comparisons. In temperate NZ, perennial ryegrass swards showed a high proportion of reproductive tillers (from 25% to 70%), a marked tiller population turnover at flowering, and an overall increase in total tiller density (Matthew et al ., ; Hernández‐Garay et al ., ; Bahmani et al ., ; Da Silva et al ., ), which is consistent with the reproductive perennation pathway being dominant. Although there is evidence that this may differ among cultivars (Bahmani et al ., ) and that tiller density can be manipulated through grazing (Thom, ; Hernández‐Garay et al ., ; Da Silva et al ., ), management appears to have little influence on the persistence strategy of perennial ryegrass (Korte, ; Matthew et al ., ).…”
Section: Discussionsupporting
confidence: 87%
“…In perennial ryegrass ( Lolium perenne L.) growing in temperate climates, the pathway of perennation has been described as ‘reproductive’ (Matthew et al ., ), which means that persistence relies on the production of daughter tillers from decapitated flowering tillers. The window of opportunity to remove flowering tillers – a management hereby referred to as ‘flowering control’ – ranges from the start of floral induction until anthesis (Korte et al ., ; L'Huillier, ; Da Silva et al ., ). A study conducted at the single tiller level by Matthew et al .…”
Section: Introductionmentioning
confidence: 97%
“…(1975) was of the same order as in this experiment (13·5 d), their long rotation was 27 d. Consequently, any impact of the reduction in herbage production on performance of cows with the short rotations would most likely have been negated in these two 3‐year studies by the reductions in herbage quality associated with the long regrowths imposed. Da Silva et al. (2004) compared shorter rotations (15 and 10 d) for 1 month with a standard rotation of 20 d, following a period of relatively lax grazing in the early part of the season, and found no difference in milk yield per cow.…”
Section: Discussionmentioning
confidence: 98%
“…As another operational rule, the initiation date which was the date when grazing started for a particular season, was very important (Da Silva et al . 2004).…”
Section: Production Of Grazing As a Consequence Of The Interface Of mentioning
confidence: 99%
“…As another operational rule, the initiation date which was the date when grazing started for a particular season, was very important (Da Silva et al 2004). Under rotational grazing systems, initiation date was shown to have a strong influence on annual herbage utilization ) and on milk production per unit area ).…”
Section: Production Of Grazing As a Consequence Of The Interface Of mentioning
confidence: 99%